The Effect Of Implemetation Of 4 Disciplines Of Execution Of Millennial Leaders In The Transformation Era On Employees’ Work Effectiveness Of PT PLN (Persero) UP3 Lhokseumawe (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to study the the effect of implemetation of 4 disciplines of execution of millennial leaders in the transformation era on employees’ work effectiveness of PT PLN (PERSERO) UP3 Lhokseumawe. This study’s population was all PT PLN (Persero) UP3 Lhokseumawe employees, totaling 144 employees. All members of the population were taken as respondents. Data were processed using structural equation modeling (SEM) for the direct influence test and the Sobel test for the indirect influence test. The research results show that wildly important goal affects work effectiveness, lead measure affects work effectiveness, compelling scoreboard affects work effectiveness, cadence of accountability affects work effectiveness, the wildly important goal does not affect organizational performance, lead measure does not affect organizational performance, coupling scoreboard affects organizational performance, cadence of accountability affects organizational performance, work effectiveness affects organizational performance, work effectiveness does not mediate the wildly important goal influence on organizational performance, work effectiveness does not mediate the lead measures influence on organizational performance, work effectiveness partially mediates the compelling scoreboard influence on organizational performance, and work effectiveness partially mediates the cadence of accountability influence on organizational performance.